2006
DOI: 10.1038/nature04860
|View full text |Cite
|
Sign up to set email alerts
|

A common mass scaling for satellite systems of gaseous planets

Abstract: The Solar System's outer planets that contain hydrogen gas all host systems of multiple moons, which notably each contain a similar fraction of their respective planet's mass (approximately 10(-4)). This mass fraction is two to three orders of magnitude smaller than that of the largest satellites of the solid planets (such as the Earth's Moon), and its common value for gas planets has been puzzling. Here we model satellite growth and loss as a forming giant planet accumulates gas and rock-ice solids from solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
390
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(418 citation statements)
references
References 40 publications
25
390
2
1
Order By: Relevance
“…Canup & Ward (2002) proposed the so-called gas-starved disk model for the formation of regular satellites of giant planets, where the satellites are formed in a waning circumplanetary disk at the very end stage of giant planet formation. Canup & Ward (2006) performed N-body simulation of satellite formation based on the above model, and showed that mass fraction of satellite system relative to the host planet is regulated to ∼ 10 −4 , which is consistent with observations. Later studies revised this model and tried to explain the difference between the satellite systems of Jupiter and Saturn (Sasaki et al 2010;Ogihara & Ida 2012).…”
Section: Introductionsupporting
confidence: 76%
“…Canup & Ward (2002) proposed the so-called gas-starved disk model for the formation of regular satellites of giant planets, where the satellites are formed in a waning circumplanetary disk at the very end stage of giant planet formation. Canup & Ward (2006) performed N-body simulation of satellite formation based on the above model, and showed that mass fraction of satellite system relative to the host planet is regulated to ∼ 10 −4 , which is consistent with observations. Later studies revised this model and tried to explain the difference between the satellite systems of Jupiter and Saturn (Sasaki et al 2010;Ogihara & Ida 2012).…”
Section: Introductionsupporting
confidence: 76%
“…The dependence of the emission power on the exomoon's crosssectional area (pR S 2 ) leads to the question of how large exomoons can be. Formation models suggest that moons can form around Jovian planets with masses up to 10 −4 times the mass of their host planet (Canup & Ward 2006;Heller & Pudritz 2015). Therefore, large exoplanets of M 3 J or larger could form a Mars-sized exomoon, and M 10 J exoplanets could have several Mars-sized exomoons or larger (Heller & Pudritz 2015) (where M 1 J is one Jupiter mass).…”
Section: Basic Mechanismmentioning
confidence: 99%
“…(31)] required to enforce coherent disk precession or maintain misalignment of the outer disk may be difficult to achieve in the context of circumplanetary disk formation (e.g. Canup & Ward 2006). Moreover, a massive disk can suffer gravitational instability.…”
Section: Discussionmentioning
confidence: 99%